Response of the Atlantic meridional overturning circulation strength to precessional forcing - Ailing Gan; Hu Yang; Xiaoxu Shi; Yi Zhong; Chunhua Qiu; Chaoyuan Yang; Jianbo Cheng; Jiping Liu (Quaternary Science Reviews, 2026)

Assessment of estuarine ecosystem health and its applications in the Yellow River estuary and the Yangtze River estuary - Zhan Wang; Ye Tian; Yunfei Gong; Dongdong Lan; Ailing Yu; Pei Fan; Xinqi Yang; Shuang Xu (Estuarine, Coastal and Shelf Science, 2026)

HYDRA-EDGE: HYDrogel-based rapid assay with entropy-driven gel enhancement for point-of-care viral detection - Ailing Yang; Li Zhou; Jing Li; Yu Liu; Ting Xiao; Qingxiang Yang; Dunquan Xu; Jiezhong Deng; Ming Chen; Sha Yang (Chemical Engineering Journal, 2026)

Protein persulfidation in plants: a central regulator of multiple signaling pathways - Di Yang; Dengjing Huang; Xinfang Chen; Ailing Li; Huan Chen; Weibiao Liao (Plant Cell Reports, 2026)

Characterization of the pathogenicity of newly emerged NADC30-Like PRRSV strains causing severe brain infections via twice inter-lineage recombination - Yuan Yang; Cheng Luo; Yixue Yan; Haoyu Chen; Feimin Xie; Ziyi Wang; Wei Wei; Mingsheng Cen; Xinyue Chen; Wenlin Huang; Xin Lan; Yu Feng; et al. (Veterinary Microbiology, 2026)

Rapid evolution of life history of two water fleas in response to inter-specific competition - Jiasheng Yang; Jianan Li; Ailing Yan; Haoran Zhang; Qianqian Wei; Xiaodong Jiang (Journal of Oceanology and Limnology, 2026)

A systematic review of anti-skin-aging collagen peptides: from source preparation and activity evaluation to multi-target mechanisms - Zhenyu Bai; Ruofang Su; Qiufang Liang; Jun Yang; Xiaohong Sun; Quan Sophia He; Arif Rashid; Ping Liu; Ailing Zhang; Xiaofeng Ren (Food Bioscience, 2026)

Defect-passivated Te-doped Cs2HfCl6 perovskite microcrystals with high efficiency and robust stability for X-ray imaging - Yanqing Zu; Run Gan; Lixia Jing; Bing Yang; Binglin Zeng; Liru Yuan; Peitao Liu; Xiaodong Li; Ailing Feng; Lei Zhou (Chemical Engineering Journal, 2026)

A multi-scale linear cross-modal fusion architecture for tomato leaf disease segmentation - Zaichun Yang; Lixiang Sun; Jinsheng Deng; Ailing Cai; Zhihuan Liu; Genhua Liu; Jiang Zhang; Guoxiong Zhou; Yahui Hu; Liujun Li (Computers and Electronics in Agriculture, 2026)

Genome-wide identification of ABC transporters and their contribution to triflumezopyrim susceptibility regulated by microRNAs in Laodelphax striatellus - Yuanxue Yang; Ailing Duan; Di Meng; Aiyu Wang; Ming Zhao; Jianhua Zhang (Pesticide Biochemistry and Physiology, 2026)

Calcium Overloading-Induced UBE2O Upregulation Alleviates Neuronal Apoptosis - Jiabin Jin; Zhuojia Yang; Ailing Kang; Yinhui Zhao; Zhuofu Cai; Minhao Qiu; Weihong Song; Yili Wu (Molecular Neurobiology, 2026)

A jetted wandering massive black hole candidate in a dwarf galaxy - Yuanqi Liu; Tao An; Mar Mezcua; Yingkang Zhang; Ailing Wang; Jun Yang; Xiaopeng Cheng (Science Bulletin, 2025)

Reducing chalkiness and enhancing quality and yield in hybrid indica rice at the middle panicle position through optimal water and nitrogen management - Yuanyuan Sun; Xiaojuan Yuan; Yinghan Luo; Guanzhou Luo; Kun Chen; Ailing Wang; Mingming Hu; Zongkui Chen; Zhiyuan Yang; Jun Ma; Yongjian Sun (Food Chemistry, 2025)

Shared e-bikes demand in urban mobility: Temporal heterogeneity, driving factors, and strategic implications - Ailing Yin; Xiaohong Chen; He Haitao; Andrew Morris; Quan Yuan; Xu Ma; Zhiwei Yang (Travel Behaviour and Society, 2025)

Preparation of a highly oil-absorbing and superhydrophobic foam based on the bionic model of dragonfly wings - Tianshui Yang; Ailing Liu; Haomiao Yang; Xiaoxuan Ju; Jingyi Kang; Xiangchi Liu; Baijun Liu; Mingyao Zhang (Journal of Environmental Chemical Engineering, 2025)

Tailored confinement-induced stress regulation in SnS@C anodes for enhanced lithium and sodium storage performance - Zhipeng Ma; Xin Yang; Ailing Song; Xinyi Zhang; Guoxing Tian; Yuqian Fan; Hao Tian; Hao Liu; Guoxiu Wang; Guangjie Shao (Chemical Engineering Journal, 2025)

Fluorination of central cores and end groups in non-fullerene acceptors for efficient organic solar cells - Yilan Zhai; Yanan Shi; Kaiming Yang; Ruixiang Fang; Huijuan Bi; Jianqi Zhang; Yanhong Chang; Ailing Tang; Zhixiang Wei; Kun Lu (Chemical Engineering Journal, 2025)

Introducing intercropping into rotation system altered the structure, function and network complexity of soil microbial communities in farmlands of the North China Plain - Gaoyuan Liu; Ailing He; Zhanping Yang; Jinling Lv; Xiuyan Pan; Nian Zheng; Jun Du (Applied Soil Ecology, 2025)

SlDCD and SlLCD increased the salt tolerance in tomato seedlings by enhancing antioxidant and photosynthesis capacity - Xinfang Chen; Dengjing Huang; Xiaoling Man; Ailing Li; Hua Fang; Siting Lu; Di Yang; Weibiao Liao (Plant Cell Reports, 2025)

Numerical Study on the Influence of Rudder Fillets on Submarine Wake Field and Noise Characteristics - Hao Yuan; Eryun Chen; Xingsheng Liu; Ailing Yang (Journal of Marine Science and Engineering, 2025)
The submarine rudder configuration and arrangement significantly impact its hydrodynamic performance. This paper takes the SUBOFF standard submarine model as the research object, constructs a geometrically parameterized rudder fillet structure based on parabolic parametric equations, and adopts the improved delayed separation vortex (IDDES) turbulence model to carry out numerical simulation research on the submarine rounding flow field with crossed and “X” rudder configurations. By comparing and analyzing the effects of different fillet parameters and rudder layouts on the generation mechanism of the horseshoe vortex, vortex system strength characteristics, and the distribution of the wake companion flow field at the velocity of 7.161 m/s, it is found that the introduction of the rudder fillet structure can effectively destabilize the horseshoe vortex and significantly reduce the axial velocity inhomogeneity of propeller plane. In addition, the improvement effect of the flow field in the near-axis region (r/R ∈ (0, 0.5)) is particularly significant. Compared with the crossed rudder, the “X” layout shows better flow control performance, with the maximum reduction in the axial relative velocity of the propeller plane surface reaching 49.34%, which is 24.25% higher than that of the SUBOFF baseline model, and the addition of two distributions of rudder fillets can reduce the hydrodynamic noise of the submarine by 4.6 dB vs. 5.6 dB at most. The results provide an essential hydrodynamic basis for optimizing the submarine rudder system.

Morphometric analysis of the female reproductive tract: influence of long-term inhalation of trace amounts of sevoflurane - Haili Wang; Haibo Qu; Ailing Yang; Daru Guo; Lili Quan; Zhaodong Liu; Xiaoli Shi; Xibo Zhao; Yuanbo Feng; Tao Liu; Hua Pan (Journal of Molecular Histology, 2025)

Construction of double-shell HPM@ATO composites with photothermal shielding capabilities and their application in thermal insulation coatings for cotton fabrics - Haomiao Yang; Xiangchi Liu; Ailing Liu; Xinyu Yao; Baijun Liu; Mingyao Zhang (Chemical Engineering Journal, 2025)

Amino oxidized sodium alginate-based humidity-resistant triboelectric nanogenerator for human motion and respiration monitoring - Xixi Wang; Na Li; Ailing Yang; Nianfeng Zhang; Wu Qiu; Dapeng Yang (Chemical Engineering Journal, 2025)

A pH-responsive MOFs@MPN nanocarrier with enhancing antifungal activity for sustainable controlling myclobutanil release - Yushan Hou; Yaowei Zhang; Yanyan Huang; Ailing Zhou; Jiatong Han; Kexin Yang; Yiming Zhao; Jie Zhou; Jing Wang; Ge Chen; Xiaomin Xu; Donghui Xu; et al. (Chemical Engineering Journal, 2024)

Creating most needed customized bus services: A collaborative analysis of user-route dynamics - Chengcheng Yu; Haocheng Lin; Yitong Chen; Chao Yang; Ailing Yin; Quan Yuan (Transportation Research Part D: Transport and Environment, 2024)

Scutellarin alleviates tensile stress-induced proliferation and migration of venous smooth muscle cells via mediating the p38 MAPK pathway - Hu Zhang; Ling Lin; Ailing Yang; Yasha Liang; Bo Huang (Tissue and Cell, 2024)

Experimental and kinetic study on pyrolysis and combustion characteristics of pesticide waste liquid - Long Yang; Zewu Zhang; Ailing Chen; Wenchao Mao; Zhengyang Zhu; Yue Zhao; Liqi Zhang (Journal of Environmental Chemical Engineering, 2024)

Granular bacterial inoculant alters the rhizosphere microbiome and soil aggregate fractionation to affect phosphorus fractions and maize growth - Xiaofan Xie; Yang Liu; Gaofeng Chen; Andéole Niyongabo Turatsinze; Liang Yue; Ailing Ye; Qin Zhou; Yun Wang; Meilan Zhang; Yubao Zhang; Zhongping Li; Lam-Son Phan Tran; et al. (Science of The Total Environment, 2024)

Green growth in the global south: How does metallic minerals affect GTFP enhancement? - Yang Liu; Ailing Wu; Jianda Wang; Farhad Taghizadeh-Hesary; Xiucheng Dong (Resources Policy, 2024)

Advances in understanding insect chitin biosynthesis - Ailing Yu; Marius Beck; Hans Merzendorfer; Qing Yang (Insect Biochemistry and Molecular Biology, 2024)

A colorimetric and fluorometric dual-mode probe for Cu2+detection based on functionalized silver nanoparticles - Guixiang Yao; Shuju Fang; Pengyuan Yin; Ailing Li; Wenrong Yang; Hongbin Wang; Wei Tan (Environmental Science and Pollution Research, 2023)

Increased ozone exposure is associated with decreased risk of epilepsy: A hospital-based study in southwest China - Yumeng Zhou; Laixin Zhou; Lili Yang; Jianghong Liu; Nan Wang; Enjie Tang; Xiaoling Liu; Chunyan Yao; Hua Xiao; Xiangjun Chen; Qian Zhang; Feng Liu; et al. (Atmospheric Environment, 2023)

Unexpected association between ambient ozone and adult insomnia outpatient visits: A large-scale hospital-based study - Dawei Li; Lili Yang; Nan Wang; Yuegu Hu; Yumeng Zhou; Ning Du; Na Li; Xiaoling Liu; Chunyan Yao; Na Wu; Ying Xiang; Yafei Li; et al. (Chemosphere, 2023)

Pyrolysis of wood waste to enhance hydrogen production on iron-based aluminum dross - Panpan Lang; Ailing Lu; Peng Liu; Yanling Li; Xueqin Li; Tanglei Sun; Yantao Yang; Tingzhou Lei (Fuel, 2023)

Molecular mechanisms of cell death in bronchopulmonary dysplasia - Xianhui Deng; Zhidan Bao; Xianpeng Yang; Yingzi Mei; Qin Zhou; Ailing Chen; Renqiang Yu; Yongjun Zhang (Apoptosis, 2023)

The Predicted Model of the Sensory Quality of Refrigerated Tilapia Skin Established Based on Characteristic Near-Infrared Spectrum - Huawei Ma; Min Lv; Zhide Ruan; Fariha Latif; Chuanyan Pan; Xu Luo; Qiong Yang; Xiaobao Qi; Yuan Zhong; Ailing Guo (Journal of Aquatic Food Product Technology, 2023)

Effects of Haematococcus pluvialis on the water quality and performance of Litopenaeus vannamei using artificial substrates and water exchange systems - Yang Wang; Mingzhu Sun; Yizhen Tang; Ailing Xu; Jingchao Tang; Zhiwen Song (Aquaculture International, 2022)

Sevoflurane inhibits the malignant phenotypes of glioma through regulating miR-146b-5p/NFIB axis - Haili Wang; Guofang Cheng; Lili Quan; Haibo Qu; Ailing Yang; Jiangge Ye; Yuanbo Feng; Xiaofang Li; Xiaoli Shi; Hua Pan (Metabolic Brain Disease, 2022)

Introduction of a multicenter online database for non-metastatic breast cancer in China - Yaping Yang; Jieqiong Liu; Min Peng; Fengxi Su; Xiaoming Xie; Zhenzhen Liu; Jundong Wu; Wei Wei; Dongxian Zhou; Weiwen Li; Ailing Zhang; Guosen Su; et al. (Science China Life Sciences, 2020)

Reference gene selection for real-time quantitative PCR normalization in Hemarthria compressa and Hemarthria altissima leaf tissue - Yao Lin; Ailing Zhang; Shengting Yang; Linkai Huang (Molecular Biology Reports, 2019)

Nuciferine alleviates LPS-induced mastitis in mice via suppressing the TLR4-NF-κB signaling pathway - Xingxing Chen; Xintian Zheng; Min Zhang; Huifang Yin; Kangfeng Jiang; Haichong Wu; Ailing Dai; Shoushen Yang (Inflammation Research, 2018)

Enhancement of brain-targeting delivery of danshensu in rat through conjugation with pyrazine moiety to form danshensu-pyrazine ester - Ailing Hui; Huayang Yin; Zheng Zhang; An Zhou; Jingchao Chen; Li Yang; Zeyu Wu; Wencheng Zhang (Drug Delivery and Translational Research, 2018)

Creation of miniature pig model of human Waardenburg syndrome type 2A by ENU mutagenesis - Tang Hai; Weiwei Guo; Jing Yao; Chunwei Cao; Ailing Luo; Meng Qi; Xianlong Wang; Xiao Wang; Jiaojiao Huang; Ying Zhang; Hongyong Zhang; Dayu Wang; et al. (Human Genetics, 2017)

Genetic diversity and evolutionary characteristics of type 2 porcine reproductive and respiratory syndrome virus in southeastern China from 2009 to 2014 - Jiankui Liu; Xia Zhou; Junqiong Zhai; Bing Li; Chunhua Wei; Ailing Dai; Xiaoyan Yang; Manlin Luo (Archives of Virology, 2017)

Distribution and quantitative detection of GABAA receptor in Carassius auratus gibelio - Jiming Ruan; Kun Hu; Haixin Zhang; Yi Wang; Ailing Zhou; Yini Zhao; Xianle Yang (Fish Physiology and Biochemistry, 2014)

Complete nucleotide sequence of a norovirus GII.4 genotype: evidence for the spread of the newly emerged pandemic Sydney 2012 strain to China - Yuqi Huo; Ailing Cai; Hui Yang; Mingli Zhou; Jiaxin Yan; Dingxiang Liu; Shuo Shen (Virus Genes, 2014)

Peat geochemical monitoring for environmental changes - Yanming Zhu; Ailing Yang; Wenyi Huo (Chinese Geographical Science, 1999)